SMART METERING DEVICE FOR HVAC SYSTEM - Maarof, M.I; Girma, T. Chala*; Hazzran, Husain; Amir, Ashraf Abdul Rahman (IAEME Publication, 2018)
This paper presents the design, fabrication and testing of a smart metering device for Heating, Ventilation and Air-Conditioning (HVAC) systems. The device was fabricated by using Arduino UNO shields combined with GSM module (SIM900A) and current sensor or current transformer (CT). The device was used to measure the power consumption of the air-conditioner. It was observed that the device can read and calculate the current flow directly from current transformer (CT). From the CT, the value of power consumption could be measured and the Arduino programming would run the calculation of the parameters and display the values on the LCD. The device was tested on the computer linked Air Conditioning laboratory unit in thermofluids lab. It can be concluded that the device can help to improvise monitoring system on air-conditioning power consumption. The device can be a handful gadget for all users to estimate their power consumption independently